PERAN MEDIA FRAGMENT DALAM METODE PEMBELAJARAN LANGSUNG TERHADAP KEBERHASILAN MAHASISWA MEMBUAT KRAR HEM: direct instruction, fragment, shirt collars - Sulistyami Sulistyami (Buana Pendidikan, 2011)
A shirt is regarded to have fine quality when the sewing technique is carried out appropriately with elegant size and shape of its collars. The present study aimed at improving the students' skills in making the quality shirt collars by using the fragment media. There were sixteen students of Dress-Making Department, taking a dressing technology course, who participated as the subjects of the study. A classroom action research with a descriptive qualitative approach was implemented in the study. The result of cycle I revealed that the students had not got accustomed to the new technique as there was no real sample for it. The result of cycle II showed that the results of the questionnaire and the assessment indicated that the use of the fragment media was effective. They showed that no one of the subjects stated that the fragment media was not of their favor. Finally, it is suggested that the fragment media in direct instruction be used to enhance the teaching and learning quality.